Implementasi Hybrid Learning PAI di UPT MPK Unsri Indralaya - Abdul Gafur; Nurhasan Nurhasan; Endang Switri; Apriyanti Apriyanti (Ideas Publishing, 2022)
After the Covid-19 pandemic, hybrid learning is the right formulation in PAI learning. The aim is to find out how the implementation of PAI learning in the Personal Development Course Technical Implementation Unit (UPT MPK) Sriwijaya University after the Covid-19 pandemic using the Hybrid model and to find out the obstacles in its implementation. The method used is descriptive qualitative research method. The results showed that this activity was quite good although there were still many things that needed to be improved because there were still many obstacles, especially the lack of existing equipment. The level of technological readiness from this research is expected to answer the challenges of educators at Sriwijaya University in particular and in general in the world of other education.